PENGARUH IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT. DAYA ANUGRAH MANDIRI - FUAD SYAKIR FUAD SYAKIR (POLITEKNIK PIKSI GANESHA, 2019)
This research was aimed to determine the influence of organizational climate and the employees’ performance at PT. Daya Anugrah Mandiri. The research method used was Based on this frame of thinking we can make the following hypothesis: organizational climate influence the Division of FATB & ASS employees’ performance at PT. Daya Anugrah Mandiri Head Office directly and indirectly. Descriptive analysis used for analize respondents response and Path analysis for influence. The used test for the research instrument is the validity test and reliability test. To change data in ordinal form, the degree of its measurement is increased in order to be interval data by using the method of Succesive interval. The outcome of this research are: In general, organizational climate at Division of FATB & ASS at PT. Daya Anugrah Mandiri Head Office have good Qualification and employees performance have high qualification. Statistic test show that organizational climate influence the Division of FATB & ASS employees’ performance at PT. Daya Anugrah Mandiri Head Office directly and indirectly.